(untitled) (Revista Española de Derecho Internacional, 2006)
Both the US and the EU are systems in which the law on international jurisdiction in civil matters shows a certain degree of uniformity against a background of different state legislations in that field. There are substantial differences between the EU and the US concerning the means used to create uniform standards or rules on jurisdiction and the scope of uniform law. Personal jurisdiction in the US is considered a constitutional issue and the key factor of uniformity is the case-law of the US Supreme Court concerning the limits imposed by the constitutional due process clause on state legislation. Those standards are mandatory to federal and state courts and they apply both to purely international cases and to US interstate cases. Moreover, they apply regardless of the nationality and domicile of the parties, even if those factors are not located in the US. However, the standards developed by the Supreme Court on personal jurisdiction are vague and the application of those standards by state courts has proven a source of uncertainty and complex litigation in many cases. There are almost no federal rules on personal jurisdiction and the long-arm statues enacted by most States are intended to reach the limits of due process and therefore they do not provide further legal certainty. In contrast with that approach, the EU has focused on uniformization by means of the enactment of common rules on jurisdiction which contribute to the mutual recognition of judgments between Member States and become a key factor to guarantee the proper functioning of the internal market and to achieve further integration in the EU. This approach is based on rules which set out common grounds of jurisdiction that must be applied in a uniform way in all Member States in order to provide a high level of legal certainty. To achieve that goal the ECJ case-law interpreting the unified rules plays an essential role. Legal certainty is a key objective of the unified rules on jurisdiction as a consequence of the role assigned to those rules in the integration process. The EU approach to international jurisdiction based on comprehensive legislative rules has advantages when compared with the US situation especially in the context of legal integration, as American scholars have acknowledged. However, the further development of the EU model should improve some of its features which are neither positive nor necessary to achieve the goals assigned to the uniform jurisdictional rules in the integration process. The development of common standards on procedural fairness in the EU should require the revision of some discriminatory aspects. Especially the application of the exorbitant fora established in the legislations of some Member States (Annex I Regulation 44/2001) to persons not domiciled in the EU and the prohibition of review of jurisdiction of the court of origin in the recognition of judgments should be reviewed. Moreover, the coexistence in the EU model of uniform rules of universal scope (such as Regulation 44/2001 and 2201/2003) with national rules which only are applied by reference of the uniform rules (art. 4 Regulation 44/2001 and art. 14 Regulation 2201/2003 concerning residual jurisdiction) is a factor of additional complexity, which could be overcome if the uniform rules were to be applied to all situations, removing totally national rules in the unified areas. That development would be in accordance with the nature of the EU Regulations in this field –especially Regulation 44/2001– as a unified and coherent system of rules on jurisdiction, as acknowledged by the ECJ in his Opinion 1/03 of February 7 2006 in order to establish that the conclusion of international agreements on jurisdiction in the areas covered by the regulations falls entirely within the exclusive competence of the EC.